Plasma Concentrations of Pregnancy‐Associated Glycoproteins Measured Using Anti‐Bovine PAG‐2 Antibodies on Day 120 of Gestation Predict Abortion in Dairy Cows Naturally Infected with Neospora caninum. Issue 4 (10th December 2012) - García‐Ispierto, I; Almería, S; Serrano, B; de Sousa, NM; Beckers, JF; López‐Gatius, F
Contents: The present study sought to determine: (i) the effects of Neospora caninum infection and twin pregnancy on plasma pregnancy‐associated glycoprotein‐2 (PAG‐2) concentrations throughout pregnancy and (ii) whether plasma PAG‐2 concentrations could predict abortion in N. caninum‐ infected cows. The study was performed on a commercial Holstein‐Friesian dairy herd in northeastern Spain and the final data included those recorded in 53 non‐aborting and 19 aborting animals. Blood samples were collected immediately before pregnancy diagnosis (on Days 40, 90, 120, 150, 180 and 210 post‐insemination) in non‐aborting cows or until the time of abortion detection in aborting cows. General lineal models (GLM) repeated measuresanova revealed the different behaviour of PAG‐1 and PAG‐2, and significant effects of Neospora seropositivity, cool season and twin pregnancy on plasma PAG‐2 concentrations throughout gestation (between‐subject effects). In addition, based on the odds ratios, the likelihood of abortion increased in Neospora ‐seropositive cows (by a factor of 7.0) compared to seronegative animals and decreased in cows with a high plasma PAG‐2 concentration (>4.5 ng/ml) on Day 120 of pregnancy (by a factor of 0.24), compared to the remaining cows. In conclusion, there is a relationship between plasma PAG‐2 concentrations and the risk of abortion in Neospora ‐infected dairy cows. Thus, plasma PAG concentrations measured using anti‐boPAG‐2 antiserum on Day 120 of gestation could serve as an indicator of the abortion risk in N. caninum infected animals; values <4.5 ng/ml indicating a high risk of abortion in chronically infected animals.